Creating Social Innovation: Lesson Learned from Community Development Practice at PT ANTAM UBP Emas Pongkor and PT Kilang Pertamina Internasional Unit III Plaju - Fitramadhana, Rizqyansyah (Indonesian Journal of Social Responsibility Review (IJSRR), 2022)
Human’s intractable problems are pushing people around the globe to create innovation. Social innovation discussions and practices had becoming global requirement that transforming the important to the future development. The government of Indonesia, through its Ministry of Environment and Forest, has inserted social innovation into their newest legal code. Permen LHK No. 1 Tahun 2021, for instance, challenges corporations to enact social innovation to sweep all the problems away. Unfortunately, that kind of expectation doesn't followed by clear instructions from the government leaving firms in a confusing situation. Spearheaded by that deficiency, this research aims to adumbrate several conditions which support the creation of social innovation. By evaluating two community empowerment-based social innovations at PT ANTAM UBP Emas Pongkor and PT Kilang Pertamina Internasional Unit III Plaju, this investigation wants to find out what is the specific precursor of social innovation. Using case study methodology, there are at least two factors contributing to social innovation in the community empowerment context. The first is scientific collaboration in the form of multidiscipline and interdiscipline. Second, social innovation needs the combination social responsibility model.